LATAR BELAKANG PENDIDIKAN SEBAGAI PREDIKTOR MOTIVASI: ANALISIS MAHASISWA DEPARTEMEN ILMU KESEJAHTERAAN KELUARGA - Mesya, Titania Dwi; Elida, Elida; Gusnita, Wiwik; Andriani, Cici (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
Abstract: Differences in educational backgrounds affect students' motivation to choose higher education study programs. This study aims to analyze the differences in student motivation between senior high school (SMA) and vocational high school (SMK) when choosing a study program. This study aims to describe and analyze the differences in motivation of students with high school and vocational education backgrounds in choosing a study program at the Department of Family Welfare Sciences. This comparative descriptive quantitative research involved 68 students, consisting of 34 students from high school backgrounds and 34 from vocational schools. Data collection was carried out through a Likert scale questionnaire with 53 questions. Data analysis used the Mann-Whitney U Test, a non-parametric statistical test, to test the difference in motivation significance. The study results show that the motivation of students from both educational backgrounds is in the medium category. However, there is a significant difference in motivation for choosing a study program. High school students tend to be more motivated by academic factors and knowledge development, while vocational school students are more concerned about practical skills and career opportunities. Statistical analysis produced a significance value of 0.031 (p < 0.05), confirming a significant motivation difference between high school and vocational school students. This study provides important insights into how educational background affects motivation for choosing study programs, which can be a consideration for curriculum development and student admission strategies in higher education.Keywords: Student Motivation, High School, Vocational School, Study Program Selection.